Aquaponics: A Way of Green Technology - Devdatta Lad (Cutting Edge Research in Biology Vol. 1, 2022)
Green technology (GT) is a broad term and a field of new innovative ways to make environmentally-friendly changes in daily life. It is created and used in a way that conserves natural resources and the environment. Aquaponics is the combination of the two agricultural practices, aquaculture and hydroponics. In aquaponics, water from the aquaculture is supplied to the hydroponics system. At the same time, the by-products are dilapidated by nitrifying bacteria, making the by-product to be utilized as nutrients by plants. The aquaculture system afterward receives the water by recirculation. If fishes are employed in an aquaponics system, the fishes are given their food, the fishes work to feed the plants, and the plants clean the water for the fishes. Aquaponics has many advantages like its sustainable, intensive food production system, needs 1/6th water to grow eight times more food per acre, and soil is not required, so no soil-borne diseases, fertilizers or chemical pesticides not required, Aquaponics can be used on non-arable lands such as deserts, degraded soil or salty, sandy islands, creates little waste and provides livelihood. Some disadvantages also exist, such that start-up costs, require expertise, daily management needed, and fish feed and electric supply add on to the input costs. Considering the advantages and disadvantages of aquaponics, it is one of the best methods available in green technology, and it will help in the conservation of natural resources.